Yoga sebagai Penanganan Kasus Hipertensi - Wirawan Tantra Pratama; I Putu Yudi Pramana Putra; Indira Vidiari Juhanna (Syntax Corporation Indonesia, 2024)
Hypertension or commonly said high blood pressure is a disease that has a high prevalence and risk of increasing other diseases simultaneously, which is listed as the main cause of death. One form of how to lower blood pressure is to provide yoga intervention, where yoga itself can regulate blood circulation that can cause blood to run smoothly and show good heart work so as to improve blood pressure control and quality of life in people with hypertension. The purpose of this research study was to find out whether yoga provides benefits in the treatment of patients with high blood pressure or hypertension. The research method used is a literature review study compiled using secondary data in the form of a review of research journals obtained from various scientific journal databases on the internet related to the effectiveness of yoga on handling cardiovascular cases in yoga practitioners. The results of the journal review that the author conducted found that the yoga variable has a positive value for reducing blood pressure or hypertension. The direction of the positive correlation obtained shows that by giving yoga intervention to hypertensive respondents will reduce blood pressure. Based on some of the literature that has been discussed, it can be concluded that the provision of yoga interventions has benefits for reducing blood pressure in people with hypertension.